Power Converter Dual Functions Using Full Bridge Converter Controlled by Microcontroller Arduino - Meptah, Muhammad Rohaizat; Kahar, Norhanan (Progress in Engineering Application and Technology, 2021)
The power converter is one of the essential components in about every aspect of our everyday lives. In order to solve this, power converter dual functions using full bridges converter controlled by Microcontroller Arduino project is proposed. The purpose of converter dual functions project is to design a multipurpose of converter that produced AC output or DC output. Microcontroller Arduino Uno based gate pulse generation technique for firing power electronic switching which is power MOSFET IRF540 powered by 12Volts DC Battery. Arduino transmit PWM signal to the gate of full bridge type of MOSFET through the MOSFET driver IR2112 used for the switching of discrete power MOSFET ON and OFF state using low voltage input in high voltage applications. PWM operation of the full bridge converter will have the high sides and low sides of the switching circuit. This converter will generate a positive voltage and negative voltage output. Push Button used for changing from DC output to AC output.